ATF6α promotes prostate cancer progression by enhancing PLA2G4A‐mediated arachidonic acid metabolism and protecting tumor cells against ferroptosis. Issue 5 (28th January 2022) - Zhao, Ru; Lv, Ye; Feng, Tingting; Zhang, Ruojia; Ge, Luna; Pan, Jihong; Han, Bo; Song, Guanhua; Wang, Lin
Abstract: Background: Despite the clinical success of androgen receptor (AR)‐targeted therapies, prostate cancer (PCa) inevitably progresses to castration‐resistant prostate cancer (CRPC). Transcription factor 6 α (ATF6α), an effector of the unfolded protein response (UPR) that modulates the cellular response to endoplasmic reticulum (ER) stress, has been linked to tumor development, metastasis, and relapse. However, the role of ATF6α in CRPC remains unclear. Methods: The effect of ATF6α on the CRPC‐like phenotype in PCa cells was evaluated by 3‐(4, 5‐dimethylthiazol‐2‐yl)−5‐(3‐carb‐Oxymethoxyphenyl)−2‐(4‐sulfophenyl)−2H‐tetrazolium inner salt (MTS), 5‐Bromo‐2‐deoxyUridine (BrdU) incorporation analysis, and cell death assay. Mechanistically, bioinformatic analysis was utilized to evaluate the potential of PLA2G4A as the target of ATF6α. Moreover, Western blot analysis, real‐time polymerase chain reaction, chromatin immunoprecipitation, arachidonic acid (AA), and prostaglandin E2 (PGE2) assays were performed to identify the regulatory effect of ATF6α on PLA2G4A. Results: In this study, we found that the increase of ATF6α expression in response to androgen deprivation generates PCa cells with a CRPC‐like phenotype. PCa cells with high levels of ATF6α expression are resistant to ferroptosis, and genetic and pharmacological inhibition of ATF6α could, therefore, promote the ferroptotic death of tumor cells and delay PCa progression. Molecular analyses linked ATF6α regulation of ferroptosis to the PLA2G4A‐mediated release of AA and the resulting increase in PGE2 production, the latter of which acts as an antiferroptotic factor. Conclusions: This study defines ATF6α as a novel antiferroptotic regulator that exacerbates PCa progression. In addition, our data establish ATF6α‐PLA2G4A signaling as an important pathological pathway in PCa, and targeting this pathway may be a novel treatment strategy.